2016
DOI: 10.1149/2.0541702jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Aspects of Interstitial Nitrogen in Carbon Steel: Passivation in Neutral Environments

Abstract: Plasma nitriding treatment was applied at 603 K to introduce interstitial nitrogen into carbon steel and to form a precipitation free nitrogen solid solution layer. The nitrogen solid solution layer contained 0.05-0.1 mass% (0.2-0.4 at%) interstitial nitrogen and resulted in ca. 0.7% expansion of the lattice parameter. Anodic polarization measurements of the nitrogen solid solution layer were taken to reveal the effect of interstitial nitrogen on the polarization behavior of carbon steel. The nitrogen solid so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…A difference of about 0.1 eV in work function indicates different kinds of metals, 45,46 and the interstitial carbon clearly resulted in a decrease in the work function of the Fe-33Mn-C steels. An increase in the work function of a carbon steel with interstitial nitrogen was demonstrated in a previous study; 31 however, the interstitial carbon led to a decrease in the work function of the Fe-33Mn-C steels in this study. Figure 9 exhibits the Fe 2p 3/2 and Mn 2p 3/2 X-ray photo-electron spectra of the 0 C and 1.1 C steels.…”
Section: Steelsupporting
confidence: 53%
See 1 more Smart Citation
“…A difference of about 0.1 eV in work function indicates different kinds of metals, 45,46 and the interstitial carbon clearly resulted in a decrease in the work function of the Fe-33Mn-C steels. An increase in the work function of a carbon steel with interstitial nitrogen was demonstrated in a previous study; 31 however, the interstitial carbon led to a decrease in the work function of the Fe-33Mn-C steels in this study. Figure 9 exhibits the Fe 2p 3/2 and Mn 2p 3/2 X-ray photo-electron spectra of the 0 C and 1.1 C steels.…”
Section: Steelsupporting
confidence: 53%
“…25,30 The enhanced corrosion resistance of carbon steel with interstitial nitrogen was demonstrated in our previous work. 31 Passivation occurred in carbon steel with approximately 0.1 mass% interstitial nitrogen in Na 2 SO 4 solutions above pH 6.0 during anodic polarization measurements, whereas carbon steel without interstitial nitrogen actively dissolved in Na 2 SO 4 solutions below pH 10.0. It was confirmed that the dissolution by-products and products of interstitial nitrogen, such as alkalization and nitrate ions (NO 3 − ), played important roles in improving the corrosion resistance of carbon steel, as in the case of austenitic stainless steels with interstitial nitrogen.…”
mentioning
confidence: 96%
“…A plasma nitride treatment on carbon steel forms a nitrogen solid solution layer on the surface which increases the corrosion resistance of the carbon steel. The anodic polarization curves show a passivation behavior (Chiba, Nagataki, & Nishimura, 2016). A plasma nitride treatment on the components of the bridge which will be in contact can prevent crevice corrosion.…”
Section: Other Researchmentioning
confidence: 93%
“…The large increase in current from ca. 1.1 V was considered to be oxygen generation [24,25]. However, for the specimen in 0.1 M NaCl-1 mM CuCl 2 , cathodic currents were measured from 0.18 to 0.23 V, and the anodic currents arose from ca.…”
Section: Pitting Corrosion Resistance Of the Specimenmentioning
confidence: 99%